Pengaruh Lingkungan Kerja dan Komunikasi Terhadap Kinerja Karyawan Di Restoran Cepat Saji Burger King Kota Harapan Indah Bekasi - Rendarisa Ramadhani; Hassanuddin Hassanuddin (CV. KAMPUS AKADEMIK PUBLISING, 2024)
. This study aims to determine the influence of the work environment and communication on employee performance at Burger King Kota Harapan Indah Bekasi. This type of research is quantitative. The sampling technique used was saturated population and sampling where the number of samples is 45 respondents who were employees at Burger King Kota Harapan Indah Bekasi. Data collection using a questionnaire and data processing using SPSS Version 26. The results of this study indicate that: (1) work environment has a significant positive effect on employee performance, (2) communication has a significant positive effect on employee performance, (3) work environment and communication have a significant positive effect on employee performance at Burger King Kota Harapan Indah Bekasi. This study provides advice to Burger King Kota Harapan Indah Bekasi, it is necessary to pay better attention to the facilities and infrastructure that support employees in carrying out their work and communication needs to be paid better attention between superiors and employees and employees with other employees in completing work.